Black art : new directions. (Stoke-on-Trent : City Museum & Art Gallery, 1989)
Kumari Burman, Chila ; Holiday, Amanda ; Lutchman, Sharon ; Row, Amrit ; Shonibare, Yinka ; Sparks, Dionne ; Sulter, Maud ; Kumari Burman, Chila ; Daley, Anthony
Black art : new directions, City Museum & Art Gallery, Stoke-on-Trent, 18 February - 27 March 1989
Engels
kunstcatalogus
Keywords: Afrika